WHAT DO STRESS CALCULATIONS REVEAL ABOUT SURFACED GEAR TEETH? - Buzauova, Toty; Smailova, Baglan; Malashkevichute-Brillant, Elena (Journal of Applied Engineering Science, 2025)
The paper focuses on the calculation of cylindrical gear transmissions using analytical and numerical methods to determine contact and bending stresses. The results of analytical calculations are compared with numerical modeling data obtained using the Ansys Workbench software environment. A comparative analysis of the results is conducted, and discrepancies between the calculations are identified. Special attention is given to the analysis of stresses in surfaced gear teeth compared to solid ones. Unlike standard calculations for solid gears, this study focuses on the stress-strain state of surfaced teeth, taking into account their operational properties. For a more detailed analysis, the concept of the ’tooth contact angle position - y’ is introduced, which allowed for an in-depth investigation of its stress-strain state. The obtained results help identify the specific behavior of restored teeth under load, which is particularly relevant for developing gear transmission restoration technologies and assessing their durability. Considering the operational properties of surfaced teeth enables a more accurate evaluation of their strength characteristics. This study is aimed at assessing the strength properties of gear transmissions with surfaced teeth and can be used to optimize their design.